A first-in-human clinical study of a new SP-B and SP-C enriched synthetic surfactant (CHF5633) in preterm babies with respiratory distress syndrome: two-year outcomes. (17th December 2022) - Sweet, David G.; Turner, Mark; Straňák, Zbynek; Plavka, Richard; Clarke, Paul; Stenson, Ben; Singer, Dominique; Goelz, Rangmar; Fabbri, Laura; Varoli, Guido; Piccinno, Annalisa; Santoro, Debora; et al.
Abstract: Objective: To assess at 24 months corrected age (CA) the neurological, respiratory, and general health status of children born prematurely from 27 +0 to 33 +6 weeks' gestation who were treated in a first-in-human study with a new fully synthetic surfactant (CHF5633) enriched with SP-B and SP-C proteins. Outcome measures: Children were assessed using Bayley Scales of Infant Development (BSID), with a score below normal defined as BSID-II Mental Development Index score <70, or BSID-III cognitive composite score <85. In addition, a health status questionnaire was used to check for functional disability including respiratory problems and related treatments, sensory and neurodevelopment assessments, communication skills as well as the number of hospitalizations. Results: 35 of 39 survivors had a neurodevelopmental assessment, 24 infants being evaluated by Bayley's Scales and 11 by health status questionnaires only. 23 children had scores within normal limits and one had BSID-III <85. The remaining 11 were judged clinically to have normal development. Health status questionnaires detected only issues that would normally be expected in preterm-born children. Conclusions: This assessment offers reassurance that treatment with CHF5633 surfactant was not associated with adverse neurodevelopmental, respiratory, or health outcomes by two years corrected age.